VOICES AND FACES: THE SIN OF CLASS DISTINCTION IN THE EPISTLE OF JAMES - Torres, Milton Luiz (Práxis Teológica, 2016)
The common belief that James did not have a well-established theological purpose when he wrote his epistle may have overshadowed the fact that his obsession for acoustic word-constructions has theological implications. An interesting case that attests to that possibility is James’s use of the word prosôpolêmpsia (“favoritism” or “class distinction”) in 2:1. My suggestion is that James paid close attention to the subject of prosôpolêmpsia or class distinction, and developed it by means of acoustic hints. By doing so, he attained the same level of tolerance to a harsh speech on the part of his audience as the moral philosophers of his time did when addressing difficult themes.